Namadzij al-Jumal Fi al-Mu’jam al-Araby Ahady al-Lughah : al-Mu’jam al-Wajeez Namudzajan: Sentences Model in Arabic Language Monolingual Dictionary: al-Wajeez Dictionary Model - Mubarok, Khusnul; Munazzalurrohmi, Muhammad; Ghatnaini, Roid Awadh Saeed Al (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2024)
This study aims to analyze sentence models in a monolingual Arabic dictionary, using Al-Wajiz as the main model. This topic was chosen due to the scarcity of dictionaries that not only provide vocabulary but also examples of sentences. This is crucial in learning Arabic, as understanding words without sentence context often does not effectively help learners grasp the true meaning and correct usage. Moreover, sentence examples assist learners in understanding how words are used in broader contexts. This study employs a qualitative method with a library research approach. The primary data was collected from the Al-Wajiz dictionary along with some supporting sources. Data was gathered through document analysis and content analysis of the dictionary. For data validation, increased diligence and peer review by experts were applied.. The results show that Al-Wajiz provides sentence examples for some words, particularly those found in the Qur'an and frequently used in daily conversations. However, there is a lack of sentence application for some words, especially nouns that do not have derived forms. In conclusion, while Al-Wajiz offers useful sentence examples, the dictionary needs further development to include more words with comprehensive sentence applications.